A dipeptidyl peptidase-4 inhibitor ameliorates hypertensive cardiac remodeling via angiotensin-II/sodium-proton pump exchanger-1 axis. (September 2016) - Kawase, Haruya; Bando, Yasuko K.; Nishimura, Kazuyuki; Aoyama, Morihiko; Monji, Akio; Murohara, Toyoaki
Abstract: Background: To address the impact of antidiabetic drugs on cardiovascular safety is a matter of clinical concern. Preclinical studies revealed that various protective effects of dipeptidyl peptidase-4 inhibitor (DPP4i) on cardiovascular disease; however, its impact of on hypertension remains controversial. Methods and results: Teneligliptin (TEN; 10 mg/kg/day/p.o.) ameliorates hypertension and cardiac remodeling by normalizing a rise of angiotensin-II (AngII) that specifically observed in spontaneously hypertensive rats (SHR). TEN had no effects on vasculature and concentrations of the DPP4-related vasoactive peptides (bradykinin, neuropeptide Y, and atrial natriuretic peptide). The primary action of TEN on BP lowering was due to restoring the AngII-induced manifestation of congestive heart failure observed in SHR. Sodium-proton pump exchanger type 1 (NHE-1) is a regulator of intracellular acidity (pHi) and implicated pathophysiological role in cardiac remodeling occurred in diseased myocardium. Cardiac NHE-1 expression level was increased in SHR and this was restored in TEN-treated SHR. AngII directly augmented cardiac NHE-1 expression and its activity that contributed to hypertrophic response. TEN attenuated the AngII-induced cardiac hypertrophy with decline in pHi via suppression of NHE-1. Loss of NHE-1 activity by specific inhibitor or RNA silencing promoted intracellular acidification and consistently attenuated the AngII-mediated cardiac hypertrophy. Conclusion: The present study revealed the protective actions of TEN on hypertension and comorbid cardiac remodeling via AngII/NHE-1 axis and the novel pathophysiological roles of intracellular acidification via NHE-1 in cardiac hypertrophy. Highlights: Distinct action of dipeptidyl peptidase-4 inhibitors on hypertension BP lowering mechanism induced by teneligliptin via non-canonical AngII pathway Novel mechanisms that modulate hypertensive cardiac hypertrophy via NHE-1 Regulatory role of intracellular acidification via NHE-1 in cardiac hypertrophy